Cytokine Profile in Patients with Herpes Zoster - O.V. Volobuieva (Journal of V. N. Karazin Kharkiv National University: Series Medicine)
Background. In recent years, increasing attention has been paid to studying cytokine levels in the blood of virus carriers and patients, as cytokines are mediators of intercellular interactions within the immune system. They influence herpes virus-infected endothelial cells, promoting enhanced expression of cellular adhesion molecules and initiating inflammatory reactions in the vascular walls. This study focuses on investigating the levels of major pro- and anti-inflammatory cytokines in patients with herpes zoster to reveal key immunopathogenetic features of inflammatory process exacerbations caused by the Varicella Zoster virus (VZV).